Design with SADSF method and analyses of elastic properties of torsion-loaded double-tee section with torsional box - Markiewicz, Ireneusz (Zielona Góra: Uniwersytet Zielonogórski)
The work presents the results of preliminary strength design of a thin-walled structure based on double-tee section loaded with a torsion moment. One of the solutions to this problem is considered, in which the torsional box is introduced in the central part. Then, one constructs a series of solution variants that differ in the torsional box length. In the design one uses the method of statically admissible discontinuous stress fields (SADSF) assuming the condition of equalized equivalent stress in the limit state.
Keywords: design; thin-walled structures; limit analysis; computer methods